COMPARATIVE ANATOMY OF CHIONINAE AND VENERINAE SPECIES (MOLLUSCA BIVALVIA: VENERIDAE) - Rocha, Valesca Paula; Matthews-Cascon, Helena (Revista Nordestina de Zoologia, 2019)
Veneridae is the most diverse and largest family in Bivalvia, with more than 500 living species. We performed a comparative anatomical analysis between six Chioninae and one Venerinae species, plus four species whose classification in Chioninae remains underexploited. The Venerinae species Chamelea gallina and the Chioninae species Anomalodiscus squamosus, Iliochione subrugosa, Leukoma thaca, Lirophora latillirata, Mercenaria campechiensis, Placamen berii, Placamen foliaceum, and Puberella intapurpurea are anatomically very similar. This comparative study complement the description of these species, with information based on soft parts comparison of mantle, siphons, digestive and nervous systems. The work also pointed differences in some structures, such as the intestine loops and how the siphons are fused. A tabular identification key was provided that also includes other species based on literature data.